Optimization Model of Learning Organization Capability and Strategic Flexibility on the Performance of Private Universities in West Java - Galih Abdul Fatah Maulani (Khazanah Sosial, 2024)
This research aims to explore data and information and understand strategic flexibility and learning organization capability in improving the performance of private universities in Indonesia. This research design uses a quantitative approach with descriptive and verification research types. The object of research involves the performance of private tertiary institutions, external environment, internal environment, learning organization, strategic flexibility, and implementation of agility programs. The survey was conducted at 81 private higher education institutions in West Java, especially those in universities or institutes. The data collection technique was carried out by proportional random sampling. The analysis used to prove the hypothesis in this study is Structural Equation Modeling (SEM) based on components or variances commonly known as Partial Least Square (PLS). The results of the descriptive analysis show that the performance of private tertiary institutions in Indonesia can be categorized as high, which means that the performance carried out by the leaders of private tertiary institutions in Indonesia can be carried out through empirical evidence. It is found that strategic flexibility influences the performance of private tertiary institutions. indicates that increasing the level of strategic flexibility implementation will improve the performance of private tertiary institutions. So that this series of models will have implications for improving performance positively and significantly.